Permeability through Caco-2 cell monolayers as a model for BBB: implementation and preliminary evaluation using model compounds - Pires, Cristiana Lages (2018)
Dissertação de Mestrado em Química Medicinal apresentada à Faculdade de Ciências e Tecnologia